Pembuatan Alat Bantu Pemasang Dan Pelepas Penambat E-Clip Berbasis Hidrolik - Atmaja, Dadang Sanjaya; Prasetya, Henry Widya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
Maintenance of the mooring system is an effort to keep the moorings on the railroad tracks in good condition. Installing and removing fastenings in Indonesia uses manual tools, namely hammers and panpullers so that it takes a long time and is less effective, so the development of the tool is aimed at minimizing the use of human labor, being more effective and not requiring a lot of time to install and remove fasteners. In this final project, the manufacture of a hydraulic-based fastening installation and release tool is carried out with the development of an old tool with a new tool. The hydraulic-based fastening installation and removal tool have a length of 105 cm, a width of 67 cm and a height of 91 cm which is able to minimize the use of human labor and is more effective in installing and removing the fasteners. The use of these tools by placing the tool on the rail and positioning the hydraulic cylinder in front of the fasteners, then pump using the hydraulic pump lever until the fasteners can be attached or removed. From the results of the development of this tool, it can be seen that the installation and removal of fasteners can be done by minimizing human labor and requires an effective time of 50 seconds.